How Does the Minimum Wage Affect Firm Investments in Fixed and Human Capital? Evidence from China - Tobias Haepp; Carl Lin (Institute for the Study of Labor (IZA), 2016)
This paper empirically analyzes the impact of Chinese minimum wage regulations on the firm decision to invest in physical and human capital. We exploit the geographical and inter-temporal variations of county-level minimum wages in a panel data set of all state-owned and all above-scale non-state-owned Chinese firms covering the introduction of the new Chinese minimum wage regulations in 2004. In our basic regressions including all Chinese firms, we find significant negative effects of the minimum wage on human capital investment rates and no overall effects on fixed capital investment rates. When grouping firms by their ownership structure, we find that these results hold for most firms. Foreign-owned firms are an exception to some extent, because the likelihood that they invest in human capital has not decreased in response to the policy.
Keywords: J31; J38; 330; minimum wage; firm investment; fixed capital; human capital